Multimedia-Aided Instruction in Teaching Grade Four Science and Health: Its Effect on Pupils’ Performance and Attitude Towards Multimedia Use in the Classroom - Galope, Virlen O. (JPAIR Institutional Research, 2013)
This study is focused on the effects of multimedia aided instructions in Grade 4 Science and health pupils’ performance and attitude towards multimedia. Specifically this study sought to explore the multimedia aided instruction on the learning environment of the grade four pupils’ performance in science and health. Two intact classes in grade 4 were exposed to multimedia aided instructions. The difference in gain scores produced by integrating multimedia in Science and Health 4 classes and those produced by conventional method of teaching was investigated in this quasi experimental research. Results indicated that using the multimedia in the classes produced significant improvement in the performance of the pupils in Science and Health, but not in the other, which is congruent with most other results for this strategy of teaching found in the literature. Follow-up survey of attitudes of 86 pupils towards the use of multimedia in the classroom provided additional evidence for its positive effect in the teaching learning process. The pupils’ attitudes towards their class were positive about the potential for multimedia and enthusiastic about what this would mean in learning Science and Health. Utilizing multimedia seemed to affect the teachers’ personal and professional growth. Teachers expect to develop their technological skills and knowledge to use multimedia in their classrooms. Pedagogical issues challenge the teachers’ approaches in the teaching and learning.